Role of Dapagliflozin and Liraglutide on Diabetes-Induced Cardiomyopathy in Rats: Implication of Oxidative Stress, Inflammation, and Apoptosis - El-Shafey, Mohamed; El-Agawy, Mosaab Salah El-din; Eldosoky, Mohamed; Ebrahim, Hasnaa Ali; Elsherbini, Dalia Mahmoud Abdelmonem; El-Sherbiny, Mohamed; Asseri, Saad Mohamed; Elsherbiny, Nehal M. (Frontiers in Endocrinology, 2022)
The current study aims to assess the protective effects of dapagliflozin (Dapa; a sodium-glucose cotransporter-2 inhibitor) and/or liraglutide (Lira; a glucagon-like peptide 1 agonist) in an experimental model of diabetic cardiomyopathy (DCM). A single dose of streptozotocin (STZ) was administrated to male Sprague–Dawley rats by intraperitoneal injection at a dose of 50 mg/kg to induce diabetes mellitus (DM). Dapa (1 mg/kg, orally), Lira (0.4 mg/kg, s.c.), and Dapa–Lira combination were administrated for 8 weeks once-daily. Blood samples were evaluated for glucose level and biochemical markers of cardiac functions. Cardiac tissue was dissected and assessed for redox homeostasis (malondialdehyde (MDA), glutathione (GSH), and catalase (CAT)), pro-inflammatory mediators (NF-κB and tumor necrosis factor-α (TNF-α)), and apoptotic effectors (caspase-3). Moreover, the effect of treatments on the cardiac cellular structure was studied. Dapa and/or Lira administration resulted in significant improvement of biochemical indices of cardiac function. Additionally, all treatment groups demonstrated restoration of oxidant/antioxidant balance. Moreover, inflammation and apoptosis key elements were markedly downregulated in cardiac tissue. Also, histological studies demonstrated attenuation of diabetes-induced cardiac tissue injury. Interestingly, Dapa–Lira combination treatment produced a more favorable protective effect as compared to a single treatment. These data demonstrated that Dapa, Lira, and their combination therapy could be useful in protection against DM-accompanied cardiac tissue injury, shedding the light on their possible utilization as adjuvant therapy for the management of DM patients.